Towards the use of sequence diagrams as a learning aid - Barros, João Paulo (2011)
Compared to imperative programing, object-oriented programming brings additional complexities. These complexities are especially challenging for the novice and, as a consequence to the teacher. Hence, it is no surprise that the teaching and learning of object-oriented programming is an extremely popular topic in computer science education research. This work in progress paper presents the objectives and structure of a tool under development for novice object-oriented programmers that intends to ease code understanding. That is accomplished through the use of sequence diagrams, one of the most popular behavior diagrams in the Unified Modeling Language (OMG, 2011), the de facto standard for object- oriented modelling. More specifically, the tool allows the generation of execution traces as sequence diagrams: for a given program run, the student is able to visualize the respective execution as a sequence diagram. Next, we present the Java2Sequence tool.